2015
DOI: 10.1039/c5ra03478g
|View full text |Cite
|
Sign up to set email alerts
|

pH sensitive smart gels of cetylpyridinium chloride in binary solvent mixtures: phase behaviour, structure and composition

Abstract: Cetylpyridinium chloride (CPC) gels from binary solvent mixtures of chlorinated solvents in the presence of water at a specific composition ratio have been studied. A transparent gel has been formed from CPC with dichloromethane, while a turbid gel with chloroform and a very weak opaque gel with carbon tetrachloride were observed in the presence of water. The CPC gel in a binary solvent mixture at a critical solvent composition of 3 : 1 v/v CHCl 3 : H 2 O has been investigated as a function of pH between 4.1-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…This is further supported by the interactions shown in the FTIR spectra of the gel, surfactant, and DES (Figure S2). Illa et al recently reported the formation of gel in the CPCl, for which they have used the binary solvent systems (CHCl 3 /H 2 O, CH 2 Cl 2 /H 2 O, and CCl 4 /H 2 O) . Similar to our work, these authors also tried gellation with several compositions of CPCl and binary solvent and discovered that, at 6% w/v, CPCl was transformed into the fibrillar gel …”
Section: Resultssupporting
confidence: 75%
“…This is further supported by the interactions shown in the FTIR spectra of the gel, surfactant, and DES (Figure S2). Illa et al recently reported the formation of gel in the CPCl, for which they have used the binary solvent systems (CHCl 3 /H 2 O, CH 2 Cl 2 /H 2 O, and CCl 4 /H 2 O) . Similar to our work, these authors also tried gellation with several compositions of CPCl and binary solvent and discovered that, at 6% w/v, CPCl was transformed into the fibrillar gel …”
Section: Resultssupporting
confidence: 75%
“…Moreover, in such a spectral range, the π-π* absorption transitions of the polyheteroaromatic structures derived from pyridinium units of the CPC head-group can also occur. Therefore, the absorption signal at 260 nm can additionally be indicative of some unreacted carbon precursor [ 46 ]. Such an attribution is confirmed by the UV-Vis absorption spectrum of a bare CPC solution ( Figure S1 ) that displays the characteristic absorption band in the UV range, while no other absorption feature can be detected in the visible portion of the spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…The objective of the present work is to investigate the self-assembly behaviour of cetyltrimethylammonium bromide (CTAB) and its gelation ability in various solvent combinations. Following our recent work [ 35 ] on pH-sensitive smart gels formed from CTAB, the present investigation explores the physico-chemical, structural and thermal properties of the CTAB gels from binary solvent mixture of toluene and water. The as-prepared CTAB gel has been organized into a lamellar gel owing to the presence of hydrophobic interactions in the proposed fibrous gel network structure [ 36 ].…”
Section: Introductionmentioning
confidence: 99%